Propuesta de implementacion de sotfware contable SIiGO en el establecimiento comercial DBC Soluciones en la ciudad de Santa Marta - Barrio Manzanares (2023)
Based from the premise that, in the economic activities of Colombia, specifically in the city of Santa Marta, it must be taken into account that the commercial sector does not make use of the necessary technology to account for their business activities, nor with accounting tools to provide support to small businesses in this sector. The project was born as a proposal for an accounting software in the company DBC Soluciones de Santa Marta - Manzanares with the objective of optimizing time and thus increase profits, reduce costs and expenses achieving an efficient control of resources. This document is a proposal for the development of a monograph, the instruments to be used will be of primary and secondary nature, in order to determine the feasibility of the implementation of an accounting software in the company DBC Soluciones. At the institutional level, this research is developed following the guidelines of accounting and its applications.